2020
DOI: 10.3389/fmicb.2020.581184
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans Membrane Vesicles Harboring Glucosyltransferases Augment Candida albicans Biofilm Development

Abstract: Candida albicans, as the most common fungus in the oral cavity, is often detected in early childhood caries. Streptococcus mutans is the major etiological agent of dental caries, but the role of S. mutans on C. albicans growth and biofilm development remains to be elucidated. Membrane vesicles (MVs) are a cell-secreted subcellular fraction that play an important role in intercellular communication and disease progression. In the present study, we investigated whether MVs from S. mutans augment C. albicans grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 67 publications
3
33
0
Order By: Relevance
“…Recent research found that MVs promoted the formation of single-strain bacterial biofilms ( Seike et al, 2020 ). The MVs from S. mutans augmented C. albicans biofilm development but had no significant effect on C. albicans growth under planktonic conditions ( Wu et al, 2020 ). However, the role of MVs and GTAs in multistrain bacterial biofilms remain unclear.…”
Section: Cooperation and Synergy In Biofilmsmentioning
confidence: 99%
“…Recent research found that MVs promoted the formation of single-strain bacterial biofilms ( Seike et al, 2020 ). The MVs from S. mutans augmented C. albicans biofilm development but had no significant effect on C. albicans growth under planktonic conditions ( Wu et al, 2020 ). However, the role of MVs and GTAs in multistrain bacterial biofilms remain unclear.…”
Section: Cooperation and Synergy In Biofilmsmentioning
confidence: 99%
“…To further investigate the effect of S. mutans MVs on C. albicans biofilm cariogenic potential, a C. albicans biofilmbovine dentin model was employed according to Sampaio et al' experimental method (Sampaio et al, 2019). S. mutans MVs have no significant effect on the pH of the C. albicans biofilm culture medium supernatants, which was reported by our previous study (Wu et al, 2020). Enamel demineralization is mainly due to the acid production of plaque biofilms (Wu et al, 2018), and C. albicans is usually detected in dentin tubules (Klinke et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…S. mutans MVs were harvested by centrifugation at 100,000 × g for 70 min at 4°C. The S. mutans MVs yield was quantified using a BCA assay (CWBIO, Beijing, China) as we previously described (Wu et al, 2020).…”
Section: Preparation Of S Mutans Mvsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.4.1.5; sucrose: 1,6-a- d -glucan 6-a- d -glucosyltransferase; dextransucrase, because they synthesize water-soluble and insoluble glucans from sucrose. They act like an invertase when hydrolyzing sucrose into glucose and fructose and as a transferase when transferring the released glucose into the growing glucan chains [ 6 ].…”
Section: Mechanism and Risk Factors Of Biofilm Formationmentioning
confidence: 99%